Being Working Poor or Feeling Working Poor? The Role of Work Intensity and Job Stability for Subjective Poverty - Marianna Filandri; Silvia Pasqua; Emanuela Struffolino (Social Indicators Research, 2020)
Low work intensity and high job instability are crucial micro-determinants of in-work poverty. Importantly, they might also affect subjective poverty in households that are above the poverty threshold. We contribute to the literature by studying the relationship between subjective and objective in-work poverty and how this relationship is affected by household members' job characteristics. We use data from the 2014 wave of the Italian module of the EU-SILC survey. Italy is an interesting case as—similarly to other Southern European countries—the share of individuals and households reporting subjective hardship is strikingly high compared to the levels reported in other EU areas. We find no statistically significant differences in the association between subjective poverty and different degrees of objective poverty by different levels of work intensity. Conversely, subjective poverty is positively associated with the instability of household members' job contracts. We argue that policies aimed at increasing work intensity rather than work stability might not help to reduce subjective poverty as well as its (negative) spillover effects on other life domains—such as well-being, adequate levels of consumption, and social integration.
Keywords: 330; in-work poverty; work intensity; job instability; subjective poverty; Italy